Tools to assess the measurement properties of quality of life instruments: a meta-review - Josep-Maria Losilla; Jaume Vives; Sonia Lorente; Carme Viladrich (BMJ Open)
Objective This meta-review aims to discuss the methodological, research and practical applications of tools that assess the measurement properties of instruments evaluating health-related quality of life (HRQoL) that have been reported in systematic reviews.Design Meta-review.Methods Electronic search from January 2008 to May 2020 was carried out on PubMed, CINAHL, PsycINFO, SCOPUS, WoS, Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) database, Google Scholar and ProQuest Dissertations and Theses.Results A total of 246 systematic reviews were assessed. Concerning the quality of the review process, some methodological shortcomings were found, such as poor compliance with reporting or methodological guidelines. Regarding the procedures to assess the quality of measurement properties, 164 (66.6%) of reviewers applied one tool at least. Tool format and structure differed across standards or scientific traditions (ie, psychology, medicine and economics), but most assess both measurement properties and the usability of instruments. As far as the results and conclusions of systematic reviews are concerned, only 68 (27.5%) linked the intended use of the instrument to specific measurement properties (eg, evaluative use to responsiveness).Conclusions The reporting and methodological quality of reviews have increased over time, but there is still room for improvement regarding adherence to guidelines. The COSMIN would be the most widespread and comprehensive tool to assess both the risk of bias of primary studies, and the measurement properties of HRQoL instruments for evaluative purposes. Our analysis of other assessment tools and measurement standards can serve as a starting point for future lines of work on the COSMIN tool, such as considering a more comprehensive evaluation of feasibility, including burden and fairness; expanding its scope for measurement instruments with a different use than evaluative; and improving its assessment of the risk of bias of primary studies.PROSPERO registration number CRD42017065232.